1996
DOI: 10.1172/jci118982
|View full text |Cite
|
Sign up to set email alerts
|

Impaired glucose homeostasis in insulin-like growth factor binding protein-1 transgenic mice.

Abstract: Transgenic mice that overexpressed IGFBP-1 are hyperinsulinemic in the first week of life and gradually develop fasting hyperglycemia. In adult transgenic mice, the hypoglycemic response to IGF-I but not insulin or des (1-3) IGF-I was attenuated ( P Ͻ 0.05) compared with wild-type mice. Furthermore, in isolated adipocytes from transgenic mice, the stimulatory effect of IGF-I but not insulin on 2-deoxy-[ 3 H]-glucose uptake was reduced ( P Ͻ 0.02). In contrast, in isolated soleus muscle, the effects of both IGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
95
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(101 citation statements)
references
References 34 publications
(43 reference statements)
4
95
0
2
Order By: Relevance
“…Burn-induced changes in the mRNA expressions of IGF-I and its binding proteins, especially IGFBP-1 and IGFBP-3, have already been shown also to result in similar changes in plasma content of their proteins (41,42). Therefore, increased mRNA expression of IGFBP-1 in liver and muscle may further dampen the activity of already reduced levels of IGF-I through inhibiting its functions (15,56,57). It has been suggested that the increase in skeletal muscle IGFBP-3 mRNA expression, and hence IGFBP-3, may also inhibit IGF-I actions (41,56).…”
Section: Discussionmentioning
confidence: 99%
“…Burn-induced changes in the mRNA expressions of IGF-I and its binding proteins, especially IGFBP-1 and IGFBP-3, have already been shown also to result in similar changes in plasma content of their proteins (41,42). Therefore, increased mRNA expression of IGFBP-1 in liver and muscle may further dampen the activity of already reduced levels of IGF-I through inhibiting its functions (15,56,57). It has been suggested that the increase in skeletal muscle IGFBP-3 mRNA expression, and hence IGFBP-3, may also inhibit IGF-I actions (41,56).…”
Section: Discussionmentioning
confidence: 99%
“…Error bars represent SE; *P Ͻ 0.05 for unpaired t-test. indicative of mild insulin resistance (36). This genetic mutation also causes glucose intolerance later in life (13).…”
Section: Discussionmentioning
confidence: 99%
“…Distinguishing between these possibilities in vivo will require additional studies involving the systemic administration of non-IGF-binding mutants of IGFBP-3. Hyperglycemia has been convincingly demonstrated after the injection of IGFBP-1 (21) in rats and in transgenic mice, which overexpress IGFBP-1 (22), however, an IGF-dependent mechanism for this phenomena has been postulated.…”
Section: Discussionmentioning
confidence: 99%